Vascular bioprinting with enzymatically degradable bioinks via multi-material projection-based stereolithography. (November 2020) - Thomas, Alexander; Orellano, Isabel; Lam, Tobias; Noichl, Benjamin; Geiger, Michel-Andreas; Amler, Anna-Klara; Kreuder, Anna-Elisabeth; Palmer, Christopher; Duda, Georg; Lauster, Roland; Kloke, Lutz
Abstract: Introduction of cavities and channels into 3D bioprinted constructs is a prerequisite for recreating physiological tissue architectures and integrating vasculature. Projection-based stereolithography inherently offers high printing speed with high spatial resolution, but so far has been incapable of fabricating complex native tissue architectures with cellular and biomaterial diversity. The use of sacrificial photoinks, i.e. photopolymerisable biomaterials that can be removed after printing, theoretically allows for the creation of any construct geometry via a multi-material printing process. However, the realisation of this strategy has been challenging because of difficult technical implementation and a lack of performant biomaterials. In this work, we use our projection-based, multi-material stereolithographic bioprinter and an enzymatically degradable sacrificial photoink to overcome the current hurdles. Multiple, hyaluronic acid-based photoinks were screened for printability, mechanical properties and digestibility through hyaluronidase. A formulation meeting all major requirements, i.e. desirable printing properties, generation of sufficiently strong hydrogels, as well as fast digestion rate, was identified. Biocompatibility of the material system was confirmed by embedding of human umbilical vein endothelial cells with followed enzymatic release. As a proof-of-concept, we bioprinted vascular models containing perfusable, endothelial cell-lined channels that remained stable for 28 days in culture. Our work establishes digestible sacrificial biomaterials as a new material strategy for 3D bioprinting of complex tissue models. Graphical abstract: Image, graphical abstract